Senior design capstone courses and ABET outcomes. - Goldberg, J.R (IEEE Engineering in medicine and biology magazine)
Capstone senior biomedical engineering design courses typically include a wide variety of lecture topics and provide students with many opportunities to develop design, communication, and interpersonal skills. This learning environment can play an important role in producing the desired ABET (Accreditation Board for Engineering and Technology)learning outcomes. Careful identification and assessment of appropriate performance indicators using the appropriate assessment tools can help a biomedical engineering program determine the role of their capstone senior design course in producing the desired ABET learning outcomes